Nilai Nilai Keagamaan Dalam Pembentukan Karakter Pada Anak Usia 4-6 Tahun Di TK Al-Itishom - Andieni, Nitha; Sianturi , Risbon; Elan, Elan; Mahmudah, Rifa (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The inculcation of religious values in early childhood is a fundamental aspect of character development, especially during the formative ages of 4 to 6 years, when children experience rapid growth in thinking patterns, attitudes, and habits that shape their future personalities. This study aims to describe the implementation of religious values in character building at TK Al-’Itishom. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The findings indicate that TK Al-’Itishom consistently integrates religious values into daily activities such as collective prayers, memorizing short Qur’anic verses, practicing greetings and smiles, instilling polite behavior, and introducing commendable conduct aligned with Islamic teachings. These practices foster the development of children’s character traits, including religiosity, discipline, honesty, and environmental awareness. The study concludes that the systematic and consistent integration of religious values in early childhood education significantly contributes to character formation. The theoretical contribution of this research lies in highlighting the role of habituation-based religious practices as a strategic model for character education in Islamic early childhood education settings, a topic that remains underexplored in current literature